Innovations in Smart Cities Applications Edition 2 The Proceedings of the Third International Conference on Smart City Applications - Ben Ahmed, Mohamed; Boudhir, Anouar Abdelhakim; Younes, Ali (Lecture Notes in Intelligent Transportation and Infrastructure, 2019)
XXIII, 1234 p. 582 illus., 467 illus. in color.